History in focus of post-classic - Myamesheva, G. Kh.; Mussalin, A.; Kindikbayeva, K. K. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
In the article the story is seen through the prism of a different viewand the gaze of the Other. Reveals the history of the concept, look,on the other. We give the concept of monumental, antiquarian and critical history of Friedrich Nietzsche. Man is an active and seeking creature, so he needs a monumental history. Human being as a protected and honored creature is in need of antique history, but as the suffering and hungry for freedom – in a critical history. Revealedthe classical andpost-classical concepts of the Other, the theory okulotsentrizmaWestern rationalism.The classical interpretation of the Other as the another of my «I» stems from Hegel’s philosophy of identity while the post-classical approach is based on the principle of distinction. The other is seen as a kind of independent structure not attached to «I» variation of the classic approach, there are several: as each other consciousness H.Ortega and Gasset, J.-P. Sartre, Husserl; Another neighbor as M.Bubera, another as a condition of possibility I dialogue with other Bakhtin, S. Frank; The other as a member of the living world and Communications Jürgen Habermas. Post-classical approach constructs the Other as structure, as a look at the world through a friend Michel Foucault, Zh.Lakana, G.Deleuze, E.Levinasa. Through these theories and concepts of the story is positioned Barrens, a new chronology, the principles of social theorist. Another view of the problem affects the reliable /unreliable in history, the history / literature, external / internal. Looking the Other-a dialogue of the new / traditional chronology,the historian / philosopher, logic / sensing. Key words: History, apprehension, other, okulocentrism, simulacrum, post-classic, type of information metabolism (TIM), the effect of reality.